ANALISIS DAMPAK KEBIJAKAN MONETER TERHADAP JUMLAH UANG BEREDAR, CADANGAN DEVISA DAN LAJU INFLASI DI INDONESIA TAHUN 2010 – 2016 - Fajarwati, Rytia Yuki; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 6, Juni 2018 (pp. 1112-1351), 2018)
Inflation is condition when prices goods and services is rising slowly and continuously. This research purpose is: 1) To know the effect of the reserve requirement, BI Rate, exchange rate, the money supply (JUB) and foreign exchange reserve to inflation rate in Indonesia. 2) To  analyze the indirect influence of the reserve requirement, BI Rate, exchange rate to inflation rate in Indonesia through the money supply (JUB) and foreign exchange reserves. This research is used secondary data with analysis of lane or path analysis. The result of this research is showed positive effect of reserve requirement on the inflation rate, BI Rate positive effect on the inflation rate, exchange rate negative effect on the inflation rate. The indirect effect showed reserve requirement and BI Rate not effected on the inflation rate through the money supply (JUB). Exchange rate effected on the inflation rate through the money supply (JUB), then BI Rate and exchange rate is effected on the inflation rate through foreign exchange reserves. Keywords: inflation, the money supply (JUB), foreign exchange reserves, reserve requirement, BI Rate, exchange rate